Novel and Functional DNA Sequence Variants within the GATA6 Gene Promoter in Ventricular Septal Defects - Li, Chunyu (MDPI, 2014)
Congenital heart disease (CHD) is the most common birth defect in humans. Genetic causes and underlying molecular mechanisms for isolated CHD remain largely unknown. Studies have demonstrated that GATA transcription factor 6 (GATA6) plays an essential role in the heart development. Mutations in GATA6 gene have been associated with diverse types of CHD. As GATA6 functions in a dosage-dependent manner, we speculated that changed GATA6 levels, resulting from DNA sequence variants (DSVs) within the gene regulatory regions, may mediate the CHD development. In the present study, GATA6 gene promoter was genetically and functionally analyzed in large groups of patients with ventricular septal defect (VSD) (n = 359) and ethnic-matched healthy controls (n = 365). In total, 11 DSVs, including four SNPs, were identified in VSD patients and controls. Two novel and heterozygous DSVs, g.22169190A>T and g.22169311C>G, were identified in two VSD patients, but in none of controls. In cultured cardiomyocytes, the activities of the GATA6 gene promoter were significantly reduced by the DSVs g.22169190A>T and g.22169311C>G. Therefore, our findings suggested that the DSVs within the GATA6 gene promoter identified in VSD patients may change GATA6 levels, contributing to the VSD development as a risk factor.